Antifungal Activity of Hair Dyes Gel from Henna Leaves and Clove Flower - Jamilatun, Makhabbah; Dewi Utami, Evi; Tolkhah, Ronal (Indonesian Journal of Pharmaceutical Education, 2025)
Henna leaves and clove flowers contain natural dyes that can be used as hair dye. Apart from that, it can also overcome dandruff problems because these plants contain antifungal activity. This study aims to determine the physical properties and antifungal activity of hair dyes gel extract from henna leaves and clove flowers. Research methods include preparing raw materials for henna leaves and clove flowers, making extracts of henna leaves and clove flowers, hair dyes gel formulation, physical properties testing, and antifungal activity testing. The hair dyes gel consists of 4 formulas, with a ratio of henna leaves and clove flowers in F0 without extract, F1 (10%: 2%), F2 (20%: 4%), and F3 (30%: 6%). Test parameters include physical properties tests which include organoleptic tests, homogeneity tests, pH tests, adhesion tests, coloring effectiveness tests, and antifungal activity tests against Candida albicans. The results of the physical properties test of the hair dyes gel showed that the combination of henna leaves extract and clove flowers can be used as a natural hair dye.  The results of the hair dyes gel inhibition test at F0 was 12.77 mm, F1 was 25.97 mm, F2 was 29.80 mm, and F3 was 32.68 mm. The gel formula that provides the best color was F3, which provides the most striking color, namely dark brown, and offers antifungal activity of 32.68 mm, with a very strong category.